THE CORRELATION BETWEEN KNOWLEDGE, ATTITUDES, BEHAVIORS, AND INCIDENTS REGARDING DENGUE FEVER AMONG FARMERS IN THE KALITIDU SUBDISTRICT, BOJONEGORO - Aracelly Putri Pribadi; Noeroel Widajati (Journal of Vocational Health Studies, 2024)
Background: Dengue Fever (DF) is a type of fever that comes on suddenly and lasts for 2 - 7 days. It is caused by the dengue virus and is spread by the Aedes aegypti mosquito. Purpose: The purpose of this research is to investigate the relationship between the level of knowledge, attitudes, and behaviors about DF and the incidence of dengue. Method: This research utilized a non-experimental, cross-sectional design with a correlational research approach. The data were collected using a probability sampling technique called simple random sampling. This research surveyed 67 family heads, who worked as farmers, to become respondents and their data were analyzed using the Chi-square test. Result: The statistical analysis using the Chi-square test resulted in p-values of 0.000055 for knowledge, 0.00001 for attitudes, and 0.003316 for behavior. All of which were significant at a level of p-value < 0.05. The findings revealed that the majority of respondents 83% had a high level of knowledge about dengue, 77% had a high level of attitudes, and 66% exhibited a high level of behaviors. Out of the 67 respondents, a large percentage 85% had not contracted dengue fever. Conclusion: There is a significant correlation between the level of knowledge, behaviors, and attitudes regarding Dengue Hemorrhagic Fever (DHF) and the incidence of dengue fever.